2020
DOI: 10.1002/jrs.6004
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐enhanced Raman scattering probe for molecules strongly coupled with localized surface plasmon under electrochemical potential control

Abstract: The light–matter interaction is the crucial tool for the efficient light energy usage. Electrochemical potential control method can tune the coupling strength between the molecules and the light field. In this study, electrochemical surface‐enhanced Raman scattering measurements have been carried out to clarify the detailed molecular behavior in the strong coupling regime. The Raman and fluorescence intensities from dye molecules in the strong coupling regime provided us the information about the change in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The results provide information about the change in the distance between the molecules and the metal surface at the angstrom level, revealing the origin of the potential dependence on the coupling strength. [ 17 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results provide information about the change in the distance between the molecules and the metal surface at the angstrom level, revealing the origin of the potential dependence on the coupling strength. [ 17 ]…”
Section: Methodsmentioning
confidence: 99%
“…The results provide information about the change in the distance between the molecules and the metal surface at the angstrom level, revealing the origin of the potential dependence on the coupling strength. [17] Li, Tian, et al prepare graphene-coated Au (Au@G) nanoparticles via chemical vapor deposition (CVD). The graphene shell thickness could be controlled from a few layers to multilayers, and the Au@G SERS activities are characterized using mercaptobenzoic acid as a probe molecule.…”
Section: Theorymentioning
confidence: 99%
“…64 We have thus attempted to actively tune the coupling strength by tuning the electrochemical potential of metal nanostructures. [65][66][67] As a strong coupling system, we have deposited dye molecules onto the plasmonic structures (Fig. 5a).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…LSPR is the collective oscillation of the free electrons in the metal nanostructures triggered by visible-light illumination. Thus, optical properties of metal nanostructures are precisely tuned by the control of their sizes, shapes, or metal species. , For example, the bowtie structure with the gap distance of less than 5 nm generates a relatively strong optical field (hot spot) at the gap. Within such plasmonic fields, various unique photoresponse phenomena, e.g., the formation of the new hybridized state, the enhancement of Raman scattering, or efficient photochemical reactions, can be induced. Our previous works have revealed that the selection rule of electronic excitation is modified by the strong localization of the light field, leading to the formation of novel excited states which are not produced by normal light illumination. In addition, very recently, we have found that the unique molecular selective condensation was observed at the hot spots under the conditions of resonant electronic excitation at an electrified interface . This molecular condensation resulted from the improvement of the light–molecular interaction under resonant conditions.…”
Section: Introductionmentioning
confidence: 99%